Single phase AC to DC converter with power factor correction using PIC controller / Sharif Muhammad Redwan Sharif Ali - Sharif Ali, Sharif Muhammad Redwan (2009)
This paper present circuit for providing power factor correction comprises an active power factor correction (PFC) and controller circuit using peripheral interface controller (PIC). In the purposed work only one power switch is employed to minimize cost, reduce switching stress and losses. By designing the necessary techniques and methodology, the overall power factor and total harmonic distortion (THD) would be improved to the expectation. Method of re-shaping the input current waveform to be similar pattern as the sinusoidal input voltage is done by the boost technique and the related controls that using the PIC controller. The PIC controller circuit is the main part of this project which provides a several -combination techniques to gain the unity power factor by sensing supply current and resolve the error created using programming and generate the desire pulse signal to drive the switch of IGBT toward controlling the charging and discharging time for boost inductor.